ANALISIS NILAI INTRINSIK PERUSAHAAN DENGAN MODEL VALUASI DISCOUNTED CASH FLOW (DCF): PERAN PROFITABILITAS DAN LEVERAGE DALAM PEMBENTUKAN FREE CASH FLOW (Studi Kasus pada Perusahaan Pertambangan Batubara Yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2024) - Mumtaz Mahal; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of profitability and leverage on the formation of Free cash flow to Equity (FCFE) and its implications for intrinsic firm value using the Discounted Cash Flow (DCF) valuation approach. The study employs a purposive sampling technique with secondary data obtained from the financial statements of three coal mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period, namely PT Bayan Resources Tbk (BYAN), PT Indo Tambangraya Megah Tbk (ITMG), and PT Bukit Asam Tbk (PTBA). The analysis uses the FCFE-based DCF valuation method through financial statement projections, cash flow estimation, terminal value calculation, and sensitivity analysis under best case, base case, and worst case scenarios.The study examines changes in profitability through variations in cost of goods sold relative to sales and changes in leverage through adjustments in the company’s funding structure. Sensitivity analysis is applied to evaluate the impact of these changes on FCFE generation and intrinsic firm value.The results indicate that profitability has a positive and significant impact on FCFE and intrinsic firm value, whereas lower profitability reduces both FCFE and firm value. In contrast, leverage shows a relatively limited effect on FCFE and intrinsic firm value under moderate conditions. These findings suggest that profitability is a more dominant factor than leverage in determining a company’s ability to generate cash flow and create intrinsic value.